Analysis of Cost of Production for Potato Pastel (Case Study: Home Industry, Palembang) - Ervina Novita (OPSI, 2021)
The home industry is a business that is managed on a small scale. The home industry is a business that is flexible and can be run by anyone who has the ability to manage their own business. One of the home industries located in the city of Palembang is the home industry. This home industry only employs 4-7 employees in its business to produce 250 pastels. In terms of financial management, this home industry does not have special bookkeeping to calculate the business it is running, so that this home industry does not clearly know the costs and benefits of this home industry. Engineering economics is a science that is studied in studying industrial engineering. Engineering economics can be used to analyze the costs and benefits of solving a problem. Technical economics can be used to evaluate finances during the home industry business process. Profits and costs are closely related to the cost of goods manufactured and the break-even point in production.